Development of a CRISPR/Cas9 genome editing toolbox for Corynebacterium stationis and its application in hypoxanthine biosynthesis - Zhilin Ouyang; Xinyu Zhang; Xinyi Hou; Jiabei Huang; Ying Lin; Suiping Zheng (Synthetic and Systems Biotechnology)
Corynebacterium stationis, a high-GC Gram-positive bacterium with significant industrial potential, has faced limitations due to the lack of efficient genetic tools. In this study, we developed a CRISPR/Cas9-based genome editing platform specifically tailored for C. stationis. First, electroporation efficiency was optimized to 1.81 ± 0.16 × 105 CFU (colony forming units)/μg plasmid DNA through medium selection, pulse parameter adjustments (2.5 kV, 2 pulses), and concentration optimization of cell wall-weakening agents (3.0 % glycine, 0.25 % isoniazid). Three functional shuttle vectors (p99E-pCG1, p19-Kan, p19-Spe) were constructed, enabling stable heterologous gene expression. By engineering a tightly regulated Cas9 expression system (Plac promoter with dual LacO∗ operators), we achieved high-efficiency genome editing, with deletion efficiencies of 81.2–98.6 % for 1.7–50 kb fragments and insertion efficiencies of 27.5–65.2 % for 1–5 kb fragments. CRISPR/Cas9-assisted ssDNA recombineering facilitated single/triple nucleotide changes with >90 % efficiency. Applying this toolbox, we engineered C. stationis for hypoxanthine biosynthesis by combining purA deletion with integration of heterologous feedback-resistant prsD128A and endogenous purF deregulation (purFK334Q), achieving a titer of 0.047 g/L. This study establishes a robust genetic platform for C. stationis, accelerating its industrial application in the production of biochemicals and biofuels.